Estimating Prevalent Diagnoses and Rates of New Diagnoses of HIV at the State Level by Age Group Among Men who Have Sex With Men in the United States. (29th May 2018) - Jones, Jeb; Grey, Jeremy A; Purcell, David W; Bernstein, Kyle T; Sullivan, Patrick S; Rosenberg, Eli S
Abstract: Background: Men who have sex with men (MSM) in the United States experience a disproportionate rate of diagnosis of HIV. Surveillance data demonstrate age-based disparities among MSM, with higher rates of diagnosis among MSM age ≤34 years nationally. Population size estimates within age group at the state level have not been available to determine rates for each state. We estimated the size of the MSM population in 5 age groups in each state and estimated the rate of prevalent HIV diagnoses in 2013 and new HIV diagnoses in 2014. Methods: We used data from the General Social Survey, American Community Survey, and previously published estimates from the National Health and Nutrition Examination Survey to estimate the population of MSM in 5 age groups at the state level. We combined these estimates with surveillance data to estimate age-stratified rates of prevalent diagnoses in 2013 and new diagnoses in 2014 in each state. We estimated standardized prevalence and diagnosis ratios comparing the Northeast, South, and West regions with the Midwest. Results: Rates of prevalent diagnoses increased with increasing age, and rates of new diagnoses were highest among younger age groups. In the United States, the new diagnosis rate among those age 18–24 years in 2014 was 1.4 per 100 MSM without a diagnosis. The highest diagnosis rates were observed among men age ≤34 years in the South. Conclusions: Age-stratified estimates of HIV prevalence and new diagnosis rates at the state level can inform public health prevention strategies and resource allocation.